Comparative Analysis of DITC Based Switched Reluctance Motor Using Asymmetric Converter and Four-Level Converter - P. Srinivas; K. Amulya (Bulletin of Electrical Engineering and Informatics, 2016)
High torque ripple is the main draw of Switched Reluctance Motor (SRM) compared to other conventional motor. Torque ripples can be minimized by Direct Instantaneous Torque Control (DITC) technique. DITC responds against the torque error instantaneously by using hysteresis torque controller and regulate the torque output of the motor within hysteresis band.This paper compares the performance of Switched Reluctance Motor in terms of torque ripples with DITC strategy for both Asymmetric converter and Four-level converter. Asymmetric converter has three states namely magnetization, freewheeling and demagnetiztion states. With four-level converter, fast magnetization and fast demagnetization are also possible. Thus, the current build up and decay time is reduced which improves the dynamic performance. SRM is simulated using DITC scheme with Asymmetric converter and Four-level converter in MATLAB/SIMULINK to analyze torque ripples and it is observed that DITC with four level converter is better than that with Assymetrical converter.